FAKTOR-FAKTOR YANG MEMILIKI KONTRIBUSI PADA KEBERLANGSUNGAN DAN KESUKSESAN UMKM YANG DIKELOLA OLEH KALANGAN USIA MUDA - Novie Noordiana RY (RELASI : JURNAL EKONOMI, 2017)
This study aims to determine the factors that affect the survival and success of the Micro, Small and Medium Enterprises (SMEs-UMKM), which is managed by the young. This study used a qualitative approach, using in-depth interview. The results showed that factors such as access to capital, social networks, competitive advantage and strategic market position, orientation on consumers, and marketing communications has a major contribution to the sustainability and success of UMKM run by young people. While the business plan does not have a major contribution to the sustainability of SMEs. The success of SMEs can be seen from the increase in turnover and operating margin in each period.